Fabrication and characterization of transparent sesquioxide laser ceramics - Yin, Danlei (Nanyang Technological University, 2020)
Sesquioxide transparent ceramics such as Y2O3, Lu2O3, and Sc2O3, have been considered as promising host materials for high powder solid-state lasers. To meet the laser applications requirements, porosity of the ceramics must be minimized to less than 0.01%. Densification of ceramics is closely related to quality of powders, sintering additives and sintering techniques.